Putting Belonging into Place: Place Experience and Sense of Belonging among Ecuadorian Migrants in an Italian Alpine Region - Raffaetà, R.; Duff, Cameron (Wiley-Blackwell, 2013)
This paper explores the meaning and mechanics of belonging with a particular focus onthe role of place and place-making. It explores the ways people come to achieve a senseof belonging with reference to recent theoretical treatments of place, territory, andmobility. We ground our discussion in analysis of an ethnographic case of Ecuadorianfamilies who have migrated to Trentino in northern Italy. Most families miss the socialrelationships and places they left behind, but have decided to stay permanently in Italy,giving up the “myth of return” (Anwar 1979). Trentino offers more opportunities interm of employment, education, and access to services than Ecuador. Yet the decisionto stay in Trentino is based on more than a simple assessment of economic advantage.Participants spoke of a slowly unfolding sense of belonging to Trentino, with strongaffective dimensions born of a specific attachment to the very materiality of place inTrentino. This attachment may be regarded as an assemblage of social, material andaffective resonances, experiences and resources, revealing something of the place andfeeling of belonging. Hence, the Ecuadorian sense of belonging does not rely on anabstract conception of cultural affiliation, nor is it a purely psychological response.Rather, belonging accrues in particular practices and material attachments.We unpackthese practices by documenting the work participants put into inhabiting an unfamiliarplace as “their” place, while at the same time questioning the ontological status of space.